#I ENVY, THEREFORE, I BUY! #: THE ROLE OF CELEBGRAM TRUSTWORTHINESS AND PARA-SOCIAL INTERACTIONS IN CONSUMER PURCHASE INTENTION - Purwanto Purwanto (Jurnal Manajemen dan Kewirausahaan, 2021)
Businessmen’s marketing strategies that take advantage of the fame of celebgrams as influencers are incredibly appropriate in the social media era. The present study deals with the dynamics of celebgram trustworthiness and social interaction with their followers in relation to possession envy and consumer purchase intention. To test the proposed model, the researchers collected data from 181 respondents in Indonesia through an online survey and analyzed it using the Smart PLS. The results of the present study showed that celebgram trustworthiness had no positive effect on possession envy but it had a positive effect on consumer purchase intention. Furthermore, parasocial interactions had a positive effect on possession envy and consumer purchase intention and possession envy had a positive effect on consumer purchase intention. The present study provides a theoretical contribution to the literature on retail and consumer services and offers managerial implications for instafamous-based marketing.